Effect of lncRNA PVT1/miR186/KLF5 Axis on the Occurrence and Progression of Cholangiocarcinoma - Sun, Qiang (Biomed Res Int, 2021)
This study primarily focused on the effect of the long noncoding RNA (lncRNA) PVT1/miR186/KLF5 axis on the occurrence and progression of cholangiocarcinoma (CCA). miR186 was found both in the lncRNA PVT1 targeting miRNAs and KLF5 targeting miRNAs using bioinformatic analysis. The expression of lncRNA PVT1 and KLF5 in the TFK-1, QBC939, and HuCCT1 cell lines and normal biliary epithelial HIBEpiC cells was detected by RT-qPCR. The significance of lncRNA PVT1 and KLF5 on cell proliferation was analyzed using the MTT assay and clone formation assay in lncRNA PVT1 and KLF5 silencing HuCCT1 cell lines and lncRNA PVT1and KLF5 overexpressing TFK-1 and QBC939 cell lines, respectively. The potential role of lncRNA PVT1 and KLF5 in cell migration was detected using the transwell invasion assay in CCA cell lines and tumor formation assay. Additionally, lncRNA PVT1 and KLF5 were proved to be highly expressed in CCA tissues and cell lines. Silencing and overexpressing of lncRNA PVT1 or KLF5 markedly inhibited or increased the cell proliferation and cell invasion in CCA cell lines, respectively. Silencing and overexpressing of lncRNA PVT1 significantly inhibited and increased the expression of KLF5 in CCA cell lines, respectively. Silencing of lncRNA PVT1 increased the expression of miR186, and silencing of miR186 increased the expression of KLF5 in CCA cell lines. Cotransfection of lncRNA PVT1 and miR186 increased the expression of KLF5 compared with controls. Overall, these results demonstrated that the lncRNA PVT1/miR186/KLF5 axis might exert a key role in the occurrence and progression of CCA, and this axis might provide a new target for treating CCA.